EFEKTIVITAS MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP HASIL BELAJAR PAI KELAS VI SD PEMBANGUNAN LABORATORIUM UNP - Andini, Suzana; Sulaiman (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research aims to determine the effectiveness of the think pair share learning model in improving student learning outcomes in class VI PAI learning at UNP Laboratory Development Elementary School. This research includes Quasi Experimental Design experimental research with random sampling techniques. The data collection method uses pretest and posttest. Hypothesis testing analysis uses Paired sample t-test and Independent sample t test. Test effectiveness using N-Gain score. The research findings show that in the paired sample t test, t count = 15.467 and significance = 0.000, so H0 is rejected, meaning that there is effectiveness of the Think Pair Share learning model in improving student learning outcomes. Then in the Independent sample t test, it was obtained that t count = 2.257 > t table = 2.08596, then H0 was rejected and significance = 0.029 < 0.05, so H0 was rejected. This means that there is a significant difference between the average scores in the experimental class (which was taught using the Think Pair Share model) and in the control class (which was taught using the conventional learning model). Next, the N-Gain Test score for the experimental class = 66.43% (quite effective). Meanwhile, the N-Gain score for the control class = 45.11% (less effective). The conclusion is that the TPS model is effective compared to conventional models in improving learning outcomes in Islamic religious education for class VI SD UNP Laboratory Development.